2008
DOI: 10.1111/j.1600-051x.2008.01325.x
|View full text |Cite
|
Sign up to set email alerts
|

Amount and type of alcohol and periodontitis in the Copenhagen City Heart Study

Abstract: The results indicate that higher alcohol consumption, particularly intake of wine, is inversely associated with CAL in men. Such an association is not found in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 24 publications
(57 reference statements)
5
38
1
Order By: Relevance
“…Although the effect of alcohol on the oral microbiota was not examined in this study, it has been shown that anaerobes were significantly reduced when the frequencies for wine and coffee drinkers were compared with the frequencies for subjects in the control group [21,29]. Our findings also agreed with a study by Kongstad et al [30] who found that higher alcohol consumption, particularly intake of wine, was inversely associated with clinical periodontal attachment level in men, but not in women. However, alcohol consumption has been found to moderately increase the severity of periodontal disease but not alveolar bone loss [31].…”
Section: Discussionsupporting
confidence: 94%
“…Although the effect of alcohol on the oral microbiota was not examined in this study, it has been shown that anaerobes were significantly reduced when the frequencies for wine and coffee drinkers were compared with the frequencies for subjects in the control group [21,29]. Our findings also agreed with a study by Kongstad et al [30] who found that higher alcohol consumption, particularly intake of wine, was inversely associated with clinical periodontal attachment level in men, but not in women. However, alcohol consumption has been found to moderately increase the severity of periodontal disease but not alveolar bone loss [31].…”
Section: Discussionsupporting
confidence: 94%
“…As determinant of periodontitis, we used a mean loss of attachment of at least 2.55 mm [27,37,38]. This may not be a precise assessment measure of the disease processes associated with periodontitis, because it only includes evidence of past tissue degeneration and not the current state of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were observed in other studies in rats [12][13] . A previous study 7 related alcohol consumption with periodontitis and obtained conflicting results, showing that higher alcohol consumption appears to have an inverse association with attachment loss in men, but not in women. The authors emphasized that further investigation is necessary to observe the association between alcohol and periodontitis, establishing prospective cohort studies with participants free of periodontitis at baseline.…”
Section: Discussionmentioning
confidence: 91%
“…However, more recent studies on humans have shown no relation between periodontal disease and alcohol consumption [6][7] . The use of rat models has been applied in the evaluation of periodontal pathogenesis 8 and regarding the influence of risk indicator/factors, such as estrogen deficiency [9][10] , alcohol consumption [11][12][13][14][15][16] , nicotine 17 and simultaneous nicotine and alcohol use 18 on disease progression.…”
Section: Introductionmentioning
confidence: 99%